2016
DOI: 10.2131/jts.41.627
|View full text |Cite
|
Sign up to set email alerts
|

Persistent neuronal apoptosis and synaptic loss induced by multiple but not single exposure of propofol contribute to long-term cognitive dysfunction in neonatal rats

Abstract: -Propofol can induce acute neuronal apoptosis or long-term cognitive dysfunction when exposed at early age in rodents, but it is unclear how the neurotoxicity including neuronal apoptosis and synaptic loss will change in a dynamic manner with brain development after multiple or single exposure of propofol, and the role of neuronal apoptosis and synaptic loss in propofol-induced long-term cognitive impairment needs to be elucidated. In this study, we investigated dynamic changes of neuronal apoptosis, neuronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…In our study, we observed that the number of TUNEL-positive neurons in the hippocampus increased in the adult rats that had been treated with propofol at young age. These, together with ultrastructural changes, including decreased levels of PSD 95 expression, widening synaptic cleft and hazing postsynaptic membrane as well as impaired spatial learning and memory, indicated that administration of high doses of propofol for a short time period induced long-term neurotoxicity, structural damages and functional impairments, similar to a previous observation with similar doses of propofol administered for a longer period 31. Indeed, injection with propofol affects the expression and proteolytic processing of crucial presynaptic and postsynaptic proteins, such as GAP-43 and MAP-2, in the cortex and thalamus of the developing brain in rats, which leads to permanent impairment of neuroplasticity and emotional behaviors 41.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In our study, we observed that the number of TUNEL-positive neurons in the hippocampus increased in the adult rats that had been treated with propofol at young age. These, together with ultrastructural changes, including decreased levels of PSD 95 expression, widening synaptic cleft and hazing postsynaptic membrane as well as impaired spatial learning and memory, indicated that administration of high doses of propofol for a short time period induced long-term neurotoxicity, structural damages and functional impairments, similar to a previous observation with similar doses of propofol administered for a longer period 31. Indeed, injection with propofol affects the expression and proteolytic processing of crucial presynaptic and postsynaptic proteins, such as GAP-43 and MAP-2, in the cortex and thalamus of the developing brain in rats, which leads to permanent impairment of neuroplasticity and emotional behaviors 41.…”
Section: Discussionsupporting
confidence: 82%
“…More recently, studies confirmed that repeated exposure to propofol induced long-term neurotoxicity in neonatal rats 9,31. In our previous study, Dex preconditioning attenuated the propofol-induced formation of acute lesions in hippocam-pal neurons in postnatal 7-day-old rats by upregulating the phosphorylation of Akt and GSK3β 28.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…In addition, it invades the mesenchyme and transfers to other sites to develop invasive carcinoma. This process forms a continuous lesion, which frequently occurs over 10 years (14). Early identification and timely treatment can substantially improve the survival rate of patients with cervical squamous carcinoma (15).…”
Section: Discussionmentioning
confidence: 99%
“…Propofol is able to induce neuronal apoptosis in young rats and cause brain dysfunction by activating the γ-aminobutyric acid receptor (27,28). Neonatal or juvenile exposure to propofol has been reported to cause learning and memory impairments in adult rats by inducing neurodegeneration and a reduction in the expression of neurotransmitters and brain-derived neurotrophic factor (BDNF) (29)(30)(31)(32)(33). In addition, prolonged exposure to propofol in aged rats also causes long-term learning and memory impairment (34,35).…”
Section: Discussionmentioning
confidence: 99%